Implementation of Occupational Safety and Health Implementation at PT. Medan Smart Jaya - Banfsya Shafa; Susilawati Susilawati (Journal of Educational Innovation and Public Health, 2024)
Occupational safety and health (K3) is an important aspect that must be considered in the workplace to maintain employee welfare and increase company productivity. This research aims to evaluate the implementation of K3 at PT. Medan Smart Jaya and its impact on employees and the company as a whole. Through analysis of the results and discussion, it is concluded that the implementation of K3 at PT. Medan Smart Jaya has provided positive results. The work safety programs implemented have succeeded in reducing the number of work accidents, reducing injury rates and increasing employee productivity. These results show that the company is committed to creating a safe and healthy work environment for all employees. However, there are several aspects that still need to be considered in order to increase the effectiveness of implementing K3 in PT. Medan Smart Jaya. First, work safety training programs need to be refined and updated regularly to remain relevant to technological and regulatory developments. Second, employees' active involvement in work safety and health efforts needs to be increased, so that they feel responsible for the safety of themselves and their colleagues. Third, routine monitoring and evaluation needs to be carried out periodically to ensure that all safety procedures and regulations are strictly followed by all employees. Fourth, companies must continue to promote a safety culture in the workplace through various means, such as providing rewards for good safety practices and improving communication about work safety issues. By taking these steps, PT. Medan Smart Jaya can continue to improve the implementation of K3, creating a safer, healthier and more productive work environment for all employees. Apart from that, the company can also strengthen its reputation as a workplace that is responsible and oriented towards employee welfare.